2015
DOI: 10.2991/icemct-15.2015.327
|View full text |Cite
|
Sign up to set email alerts
|

Governing the knowledge sharing for repatriates with SECI model An empirical test

Abstract: Abstract. Knowledge sharing of repatriates is embedded in a complex project environment and affected by the organizational knowledge governance mechanisms. This paper seeks to find out the mechanisms that promote repatriates to share their knowledge achieved in international construction projects after returning to domestic projects. We collect data from 245 respondents in 33 Chinese contractors. The test results indicate that adoption of knowledge governance mechanisms influence repatriates' knowledge sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The first hypothesis, we hypothesized that socialization is positively associated with organizational knowledge creation and sharing, results suggest that this hypothesis held true. This claims socialization has a significant direct influence on organizational KCS in New Zealand, which is supported by previous research (Li & Zhang, 2015: 1544Ramirez & Morales, 2011: 444;Tan, Lye, Ng, & Lim, 2010: 192;Travaille & Hendriks, 2010: 423).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The first hypothesis, we hypothesized that socialization is positively associated with organizational knowledge creation and sharing, results suggest that this hypothesis held true. This claims socialization has a significant direct influence on organizational KCS in New Zealand, which is supported by previous research (Li & Zhang, 2015: 1544Ramirez & Morales, 2011: 444;Tan, Lye, Ng, & Lim, 2010: 192;Travaille & Hendriks, 2010: 423).…”
Section: Resultssupporting
confidence: 79%
“…The second and fourth hypothesis, hypothesized relationships were outlined as: knowledge combination is positively associated with organizational knowledge creation and sharing, internalization is positively associated with organizational knowledge creation and sharing. Although the literature reviewed suggested that knowledge combination, internalization (Li & Zhang, 2015: 1544Chaikrongrag & Angkasith, 2010: 218;Tan, Lye, Ng, & Lim, 2010: 192) results suggest these hypotheses are not supported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation